Proceeding of 3rd Thermal and Fluids Engineering Conference (TFEC) 2018
DOI: 10.1615/tfec2018.tfl.021662
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Turbulence Models for Flow in a Constricted Pipe at Low Reynolds Number

Abstract: Computational fluid dynamics (CFD) is a useful tool for prediction of turbulence in aerodynamic and biomedical applications. The choice of appropriate turbulence models is key to reaching accurate predictions. The present investigation concentrated on the comparison of different turbulence models for predicting the flow field downstream of a constricted pipe. This geometry is relevant to arterial stenosis in patients with vascular diseases. More specifically, the results of Unsteady Reynolds-Averaged Navier-St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…CFD may also provide valuable information to speed up the design of implantable devices during the prototype development [ 29 ] and reduce the costs and risks associated with new heart valve designs [ 30 ]. Hence, analysis of flow dynamics and the resulting turbulence [ 31 , 32 , 33 , 34 ] and sounds [ 35 , 36 , 37 , 38 , 39 , 40 ] has been an active area of research.…”
Section: Introductionmentioning
confidence: 99%
“…CFD may also provide valuable information to speed up the design of implantable devices during the prototype development [ 29 ] and reduce the costs and risks associated with new heart valve designs [ 30 ]. Hence, analysis of flow dynamics and the resulting turbulence [ 31 , 32 , 33 , 34 ] and sounds [ 35 , 36 , 37 , 38 , 39 , 40 ] has been an active area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease is a leading cause of death in the world. Analysis of blood flow dynamics [20]- [26] and heart related signals might result in improving current diagnostic methods, and eventually decreasing the mortality rate associated with cardiovascular disease. Cardiac time intervals (CTIs) have been widely used as clinical metrics for cardiovascular diagnosis.…”
Section: Application In Cardiovascular Diagnosismentioning
confidence: 99%
“…Detailed description of the mesh, CFD model and validation against LDA measurements can be found in previous studies. [7][8][9] A time step of 0.0001 seconds was used in the simulations. The density and the dynamic viscosity of the air were selected as 1.184 kgm -3 and 1.855×10 -5 Pa.s, respectively.…”
Section: Computational Modellingmentioning
confidence: 99%
“…Here, the minimum value of the velocity scale is limited to 1 ms -1 to get a clear representation of the different flow regions observed in the flow domain, which were similar to previous studies, 13,14 More details about CFD results can be found in the previous study. 8 A volumetric representation of the APE acoustic sources (source term: Figure 2B. The acoustic sources seem to appear from the edges of the constriction and stay as more organized structures in the "flow jet and separation region".…”
Section: Computational Modellingmentioning
confidence: 99%
See 1 more Smart Citation